Fintech entry, firm financial inclusion, and macroeconomic dynamics in emerging economies - Alan Finkelstein Shapiro; Federico S. Mandelman; Victoria Nuguer (Federal Reserve Bank of Atlanta, 2022)
We build a model with a traditional banking system, endogenous entry of firms and fintech intermediaries, and firm heterogeneity in credit access and usage to study the credit-market, macroeconomic, and business cycle implications of the recent sizable growth in the number of fintech intermediaries in emerging economies. Our analysis delivers three findings. First, the impact of greater fintech entry on firm financial inclusion depends on whether greater entry is driven by lower entry costs for fintech intermediaries or lower barriers to fintech credit for unbanked firms. Second, greater fintech entry can have positive long-term macroeconomic effects. Third, greater fintech entry leads to a reduction in output volatility but results in greater relative volatility in bank credit and consumption. The effects of fintech entry on macro outcomes and volatility hinge critically on the interaction between domestic financial shocks and the reduction in fintech lending rates stemming from greater fintech entry. Unless greater fintech entry leads to lower fintech credit costs for firms, greater fintech entry will have no meaningful credit-market or business-cycle consequences.
Keywords: E24; E32; E44; F41; G21; 330; financial access and participation; endogenous firm entry; banking sector; fintech entry; emerging economy business cycles